Comparing home-grown fruits: productivity convergence across industries and regions - Stein Ostbye; Olle Westerlund (European Regional Science Association (ERSA), 2003)
Output per worker is radically unevenly distributed across space. Several authors have asked why the differences are so large between countries and hypothesized that differences in social infrastructure provide an answer. However, differences in output per worker are also very different when comparing spatial units at lower levels of resolution without substantial variation in social infrastructure. The purpose of this paper is to discuss possible reasons why. We will do so by looking at regional data for the Scandinavian Peninsula at a spatial resolution equivalent to the European NUTS3. Since Norway and Sweden is considered particular egalitarian and homogeneous societies, differences in broad measures of social infrastructure can hardly be invoked as substantial important determinants of productive performance. Instead we suggest that differences in industrial structure and human capital are able to explain the differences we observe.
Keywords: 330